Erythrocyte profile in cordblood of newborns to diabetic and non-diabetic mothers - Thaseen, Nazima; Veeraiah, Shivakumar (International Journal of Research in Medical Sciences, 2021)
Background: Diabetes, an endocrinal disorder causing morbidity and mortality has its effect on gestational diabetes. Intrapartum stress, maternal hyperglycemia leads to fetal hyperglycemia. The maternal glycaemic status has influence on neonates erythrocyte profile. Methods: Cord blood of neonates born to 40 diabetic (known to be diabetic at pregnancy) and 40 non-diabetic mothers were selected. A fully automated hematology analyzer ABXMICROsot was used to analyze whole blood collected in EDTA tubes. The diabetic group was subdivided into D1 and D2. D1 as 100-150 mg/dcl, D2 as above 150 mg/dcl. Results: Hemoglobin, hematocrit, MCV, MCH, RDW were significantly higher, RBC count were comparatively insignificant. Hemoglobin (Hb), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), Mean corpuscular hemoglobin concentration (MCHC) were significantly higher in D2 than D1 group. The prognosis for the child of a pregnant diabetic is related to the degree of control of mother’s glycemic status, reflected as higher indices in D2 than D1. Conclusions: Neonatal immune system depends on maternal immune system i.e, all the immunological properties are practically under the control of interleukin-1 and interleukin-6. Interleukin-6 potentiates the action of interleukin-1 synergistically, such action of interleukin converts noncommitted stem cells to committed stem cells. Immunosuppressant status in diabetic mother (i.e., non-priming of neonatal interleukin-6 by immunosuppressant diabetic mother`s interleukin-6, the main cause for these altered count). By modulating neonatal interleukin-6 it decreases hematopoietic potential in the neonates, on the other hand ECF in infants of diabetic mother is reduced leading to hemoconcentration and increase in cell counts. Giving a picture as if polycythemia at birth in neonates of diabetic mothers.